Solicitação de refúgio como estratégia migratória dos venezuelanos em Roraima nos anos de 2014 a 2017 - Abrahão, Bernardo Adame (2019)
The present dissertation studies the phenomenon of refugee requests by Venezuelans in the state of Roraima under the bias of the migratory strategy drawn by the refugees taking into account the motivation of the displacement and the causes, to then analyze the options made by the refugees in the request of the legal reception and political in the state of Roraima. By migratory strategy, it is understood choice of request of refuge in a certain place, in the limitation of the research, Roraima. Migration theories collated with data on Venezuelan migration in Roraima from 2014 to 2017 will allow the conclusion that Venezuelans represent a survival migration. Migration that does not yet have adequate legal support to protect and guarantee the migrants' human rights, which leaves them most vulnerable. Punctual and precarious regulations do not serve due harvest, especially due to the lack of adequate and clear immigration policy. It is imperative that this migratory flow is observed and regulated in order to comply with the human rights of the migrant.